Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let the random variable $X$ have the $N(0,1)$ distribution for which the probability function is: $$ f(x)= \frac{1}{\sqrt{2\pi}}\exp\left(-\frac{x^2}{2}\right), -\infty< x <\infty $$ Let $Y=e^X$.

A. Find the probability density function for $Y$,

B. Find $E(Y)$,

C. Find $E(Y^2)$ and deduce $\mathrm{Var}(Y)$.

B and C I can do if I find A but can anybody explain to me how this is done. The logic behind it.

share|improve this question

2 Answers 2

To find the density function $f_Y(y)$ of $Y$, one strategy is to find the cumulative distribution function $F_Y(y)$, and then differentiate. Note that $Y$ is always positive, so $F_Y(y)=0$ if $y\le 0$. Now suppose that $y\gt 0$. Then $$F_Y(y)=\Pr(Y\le y)=\Pr(e^X\le y)=\Pr(X\le \ln y).$$ Thus $$F_Y(y)=\int_{-\infty}^{\log y}f(x)\,dx.$$ To find the density, differentiate. We do this by differentiating under the integral sign, that is, by using the Fundamental Theorem of Calculus. We get $$f_Y(y)=\frac{1}{y}f(\log y).$$

Remark: To find $E(Y)$, I would suggest not using the density. Easier, I think, is to use $$\int_{-\infty}^\infty e^x f(x)\,dx.$$ Apart from a constant, we are integrating $e^{-(x^2-2x)/2}$. Complete the square, and make the substitution $u=x-1$.

share|improve this answer

The cumulative distribution function of $Y$ is $$F_Y(y)=P(Y\leq y)=P(e^X\leq y)$$ which is $0$ when $y\leq 0$, and when $y>0$ then $$ P(e^X\leq y)=P(X\leq\log(y))=\int_{-\infty}^{\log(y)}f_X(x)\,\mathrm dx=F_X(\log(y)). $$ Differentiating $F_Y(y)$ we obtain the density of $Y$: $$ f_Y(y)=F'_X(\log(y))\frac{1}{y}=f(\log(y))\frac{1}{y}=\frac{1}{y\sqrt{2\pi}}\exp\left(-\frac{\log(y)^2}{2}\right),\quad y>0, $$ and $f_Y(y)=0$ for $y\leq 0$.

share|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.